2019
DOI: 10.31685/kek.v3i1.409
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesuksesan Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) pada Satuan Kerja di Lingkungan Badan Pendidikan dan Pelatihan Keuangan (BPPK)

Abstract: Penelitian ini dilakukan dengan tujuan untuk menganalisis dan mengukur sejauhmana kesuksesan implementasi SAKTI yang telah berjalan selama ini berdasarkan sudut pandang pengguna (user) sebagai sistem yang bersifat mandatory pada satker di lingkungan Badan Pendidikan dan Pelatihan Keuangan (BPPK). Sumber data yang digunakan dalam penelitian ini berasal dari data primer berupa data yang diperoleh dengan metode survei dengan mengirimkan kuesioner kepada para user SAKTI. Dengan teknik purposive sampling dan pendek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 18 publications
6
8
0
6
Order By: Relevance
“…From table 8 above, it is concluded that the effect of the user satisfaction variable on net benefits is positive and significant, which means that H4 is accepted. The results of this hypothesis are in line with the research of Hidayatullah, et al (2020), Amriani & Iskandar, et al (2019) and Rahayu, et al (2018). Satisfaction is a feeling of pleasure and joy felt by someone after buying or using a product, either goods or services from the company.…”
Section: H3: Service Quality Has a Positive And Significant Effect On...supporting
confidence: 91%
See 2 more Smart Citations
“…From table 8 above, it is concluded that the effect of the user satisfaction variable on net benefits is positive and significant, which means that H4 is accepted. The results of this hypothesis are in line with the research of Hidayatullah, et al (2020), Amriani & Iskandar, et al (2019) and Rahayu, et al (2018). Satisfaction is a feeling of pleasure and joy felt by someone after buying or using a product, either goods or services from the company.…”
Section: H3: Service Quality Has a Positive And Significant Effect On...supporting
confidence: 91%
“…From Table 8 above, it can be concluded that H1 is accepted. In line with research conducted by Amriani & Iskandar (2019), Hidayatullah, et al (2020) and Rakhmadian, et al (2017). System quality is the technical quality in an information system which is a combination of software and hardware in the information system.…”
Section: Hypothesis Testing (T-test)supporting
confidence: 90%
See 1 more Smart Citation
“…Results of several studies have supported this statement and found a strong relationship between system quality and information system user satisfaction. The studies that confirm this finding are; (Sumiyati et al, 2013;Amriani, & Iskandar, 2019;Choi et al, 2016;Hidayat, 2019;Bahesa, 2018;Irfan, 2019). The positive direction of influence means that the higher the quality of the system is, the higher the user satisfaction will be.…”
Section: Methodsmentioning
confidence: 80%
“…Therefore, the measurement of use in a mandatory system cannot accurately reflect the user's reaction to the information system (Amriani, T. N., & Iskandar, 2019). Adopting Delone and McLean's model of success 2003, the relationship between the variables tested, based on user responses, in terms of system quality variables available on the e-Filing system with flexible system indicators, is considered reliable because the variables are integrated with other systems.…”
Section: Introductionmentioning
confidence: 99%